Theoretical Study on Corrosion Inhibition Properties of 2-Isopropyl-5-Methylphenol - Saprizal Hadisaputra; Saprini Hamdiani; Eka Junaidi (ALCHEMY Jurnal Penelitian Kimia, 2016)
Corrosion inhibitors of 2-isopropyl-5-methylphenol and its derivatives has been elucidated by means of density functional theory at B3LYP/6-31G(d) level of theory. Effect of electron donating and withdrawing groups such as NH2, SH, CHCH2, CH3, OH, CHO, COOH, F and NO2 on the corrosion inhibitor of 2-isopropyl-5-methylphenol derivatives also have been studied. The quantum chemical parameters such as the frontier orbital energies (EHOMO), ionization potential (I), electron affinity (A) and electronegativity (χ) are closely related to the corrosion inhibition efficiency (IE %) of 2-isopropyl-5-methylphenol derivatives. The presence of electron donating groups increase IE % values meanwhile electron with drawing groups reduce IE % values. The enhancement of IE % follows NO2 < CHO < COOH < SH < F < CH3 < CHCH2 < OH < NH2. Electron donating NH2 group gives 96.38 % of IE %, pure 2-isopropyl-5-methylphenol IE % = 82.70 %. In contrast, electron withdrawing NO2 group gives IE % only 68.66 %. This theoretical study would have a significantly contribution for accelerating corrosion inhibitor experimental to gain optimum results.